Focal dystonia, tremor and myokymic discharges secondary to electrical injury - Konstantina G. Yiannopoulou; Theodoros Avramidis; Roxani Divari; Alexandros Papadimitriou (MDPI AG, 2009)
We describe the case of a male patient who developed electromyographically confirmed myokymia, dystonia and tremor and clinically confirmed focal dystonia and tremor, secondary to electrical injury. Dystonia is a rare complication of electrical injury. Myokymic discharges secondary to electrical injury are previously unreported. Dystonia and tremor EMG findings were present not only at the clinically affected muscles of the lower limb but also at the clinically unaffected upper limb muscles. This is the first case report to link myokymia as a secondary complication of an electrical injury.